Auditor switch decision of Malaysian listed firms: tests of determinants and wealth effect - Ahmed, Huson Joher Ali; Ali, M.; Ramadilli Mohd, Shamsher Mohamad; Md Nassir, Annuar; Syed Mohamed, Mohamed Ariff (Universiti Putra Malaysia Press, 2000)
This article examines the economic rationale for auditor change by Malaysian listed firms by examining audit switch effect on share prices. The auditor change decision by management to retain or to change involves a switch across audit firms with different quality. Audit quality is defined by classifying the audit firms into Tier 1 (Big-5) firms and Tier 2 (non-Big 5) firms. The distinguishing attribute between the two groups of audit products is believed to be the credibility that each group brings to the audit engagement. Factors associated with the choice of audit firm and changes for firm characteristics associated with auditor choice were investigated using the logistic regression model. The findings show that the auditor switch of Malaysian listed firms is partly explained by changes in management and turnover growth. Changes in firms' characteristics such as asset growth, purchase of fixed asset to total asset, leverage and changes in financing activities explain auditor switches. There appears to be no evidence of significant wealth effect from auditor switch announcements.